Chronotypes in elite Japanese athletes: assessed by the reduced Morningness-Eveningness and Munich ChronoType Questionnaires - Hoshikawa, M. (Chronobiology International, 2021)
This study aimed to test in elite athletes the correlation between the chronotype determined by the reduced version of the Morningness-Eveningness Questionnaire (rMEQ) and that determined by the Munich ChronoType Questionnaire (MCTQ). In total, 351 elite athletes filled out the rMEQ questionnaire, 59 athletes filled out the MCTQ questionnaire, and 39 athletes filled out both questionnaires. The rMEQ score and the corrected midpoint of sleep from the MCTQ correlated weakly (|r| = 0.360, p < .05); however, some cases were mismatched. The MSFsc also weakly correlated with age (|r| = 0.374, p < .05), while rMEQ did not. Our results may suggest that the choice of questionnaire to determine chronotype should depend on the purpose and the type of sport athlete.